The crystal structure of 6-(benzofuran-2-yl)-2-oxo-4,5-diphenyl-3,4-dihydro-2H-pyran-3-carbonitrile, C26H17NO3 - Liu Miao-Chang; Huang Xiao-Bo; Wu Deng-Ze (Zeitschrift für Kristallographie - New Crystal Structures, 2024)
C26H17NO3, monoclinic, Cc (no. 9), a = 20.044(2) Å, b = 10.7294(9) Å, c = 9.4232(8) Å, β = 91.689(3)°, V = 2025.6(3) Å3, Z = 4, Rgt(F) = 0.0360, wRref(F2) = 0.0814, T = 293(2) K.